Tingkat Kenyamanan Pengguna Lahan Parkir Roda Dua Di Lecture Building Fakultas Teknik Universitas Mulawarman - Airfandylaga Arrosyidhan; Arisa Aulia Rahmitasari Sukardi; Indra Ariani; Pandu K. Utomo; Sartika, Dewi (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2023)
The Lecture Building of the Faculty of Engineering, Mulawaran University is located on Jalan Sambaliung and is a newly operating lecture building, this building provides parking space for two-wheeled and four-wheeled vehicles. Judging from the condition of the two-wheeled parking area, it looks uncomfortable because there are several entry and exit lanes that are quite narrow, so if the atmosphere is busy and there are two vehicles that meet from two opposite directions, they have to yield to each other. The method applied in this study is to use quantitative and qualitative methods by conducting a site survey to determine conditions in the field and distributing Likert-scale questionnaires to determine the user's comfort level.The results of the analysis obtained by the measurements in the parking area are many that are not in accordance with the Decree of the Director General of Land Transportation No. 272 ​​of 1996 concerning Technical Guidelines for the Implementation of Parking Facilities, there are only a few points that comply with the standards. Convenience in the parking area is somewhat uncomfortable even though the parking area capacity is sufficient and the parking area distance to the campus building is close, but some students stated that they had difficulty getting out, driving and placing their vehicles, the size of the circulation path was narrow, the security in the parking area was not good and there is no CCTV. The parking area is clean but at certain times it smells bad, there is lighting in the form of garden lights even though the lights are not bright and there are signs or markings even though some of the markings have faded.